THE STATE AND CIVIL SOCIETY IN THE GENERAL PROGRESS OF CIVILIZATION - Черноног, Р. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2021)
In clause the coTparative analysis of mutual relation of the state and society is given. Thus the state is considered as universal institute, which should serve nation- wide and national interests.